Prediction of Creativity Level Based on Indicators of EEG With the use of Neural Network Models - Kozachuk, Nataliia O.; Gurianov, V.G.; Kachynska, Tetiana V.; Shvarts, Liudmyla O.; Poruchynskyi, Andrii I.; Dmytrotsa, Olena R.; Abramchuk, Olha M.; Козачук, Наталія Олександрівна; Гуріанов, В. Г.; Качинська, Тетяна Валеріївна; Шварц, Людмила Олексіївна; Поручинський, Андрій Іванович; et al. (Research Journal of Pharmaceutical, Biological and Chemical Sciences, 2015)
This paper proposes a method of diagnosis of the creativity level based on indicators of the electrical activity of the cerebral cortex, which was developed by using artificial neural network. It was established that the probability of a high level of creativity is connected with the speed of decision-making; value of the coherence coefficient between the left anterior frontal and left occipital areas of the EEG alpha-2-range, the focus of interaction in the right posterior-temporal area in the delta range and the focus of interaction in the right parietal area of the beta range.
Прогнозування рівня креативності на основі показників ЕЕГ з використанням моделей нейронних сіток
Keywords: artificial neural network; statistical moment; creativity; electrical activity of the cerebral cortex